ANALISIS ELEMEN HINGGA UNTUK FAKTOR KONSENTRASI TEGANGAN PADA PELAT ISOTROPIK BERLUBANG DENGAN PIN-LOADED - Hartini, Dwi (Sekolah Tinggi Teknologi Adisutjipto, 2016)
Hole in the structure is often a serious problem, because the hole would trigger a surge in stress concentration which resulted cracks in the structure. In this research will analyze the stress concentration factor on isotropic plate with hole. The method used is numeric method. The technique used to collect data is the study of literature and comparative study of several similar research. Then the design is modeled and analyzed using Patran/Nastran. Based on this analysis the final result obtained is a mathematical equation that can be used to predict the stress concentration factor at the isotropic plate with hole where the results approached to Peterson distribution is used as reference in this research.